Assessment of bronchodilator responsiveness in preschool children using forced oscillations. Issue 9 (5th April 2007) - Thamrin, Cindy; Gangell, Catherine L; Udomittipong, Kanokporn; Kusel, Merci M H; Patterson, Hilary; Fukushima, Takayoshi; Schultz, André; Hall, Graham L; Stick, Stephen M; Sly, Peter D
Abstract : Background: The forced oscillation technique (FOT) requires minimal patient cooperation and is feasible in preschool children. Few data exist on respiratory function changes measured using FOT following inhaled bronchodilators (BD) in healthy young children, limiting the clinical applications of BD testing in this age group. A study was undertaken to determine the most appropriate method of quantifying BD responses using FOT in healthy young children and those with common respiratory conditions including cystic fibrosis, neonatal chronic lung disease and asthma and/or current wheeze. Methods: A pseudorandom FOT signal (4–48 Hz) was used to examine respiratory resistance and reactance at 6, 8 and 10 Hz; 3–5 acceptable measurements were made before and 15 min after the administration of salbutamol. The post-BD response was expressed in absolute and relative (percentage of baseline) terms. Results: Significant BD responses were seen in all groups. Absolute changes in BD responses were related to baseline lung function within each group. Relative changes in BD responses were less dependent on baseline lung function and were independent of height in healthy children. Those with neonatal chronic lung disease showed a strong baseline dependence in their responses. The BD response in children with cystic fibrosis, asthma or wheeze (based on both group mean data and number of responders) was not greater than in healthy children. Conclusions: The BD response assessed by the FOT in preschool children should be expressed as a relative change to account for the effect of baseline lung function. The limits for a positive BD response of −40% and 65% for respiratory resistance and reactance, respectively, are recommended.